Research on Accessibility Evaluation Method for Urban Rail Transit Station Based on Shared Bicycle Connection - Yuhui ZHANG; Yu CAO; Yanjie JI (Chengshi guidao jiaotong yanjiu, 2024)
[Objective] The shared bicycle is an effective connection tool for urban rail transit station. It is necessary to establish an accessibility measurement model to evaluate the accessibility of urban rail transit stations based on shared bicycle connection. [Method] Based on the data of shared bicycle transport and urban rail stations in Nanjing, the riding time, riding distance and the transfer volume of shared bicycles at each station are statistically analyzed, and the riding distance is selected as the accessibility evaluation index. The indicators such as mobility, convenience, accessibility and the impact factors of station scale are calculated, and an urban rail station accessibility measurement model based on shared bicycle connection is established. A cluster analysis of urban rail stations in Nanjing is carried out, and the accessibility measurement and evaluation of urban rail stations based on shared bicycles connection are carried out. [Result & Conclusion] From the regional perspective, the accessibility value is generally higher in the downtown area, and is widely distributed in suburban areas, and generally low in the outer suburbs. From the perspective of the station type, the accessibility measurement value of the stations with comprehensive function is generally high, followed by office-oriented stations and residence-oriented stations. The accessibility measurement values of the stations away from office and residence and other types are generally low.